Scraping the bottom of the barrel? Evidence on social mobility and internal migration from rural areas in nineteenth-century Norway. Issue 3 (2nd September 2022) - Moilanen, Mikko; Myhr, Sindre; Østbye, Stein
ABSTRACT: We aim to answer whether expected occupational gains motivated rural-urban and rural-rural migration in nineteenth-century Norway. Human capital theory indicates that the higher expected gains, the more prone an individual will be to migrate. We use a micro-level data set of over 42, 000 rural sons linked to their fathers based on 1865 and 1900 Norwegian censuses and employ a switching endogenous regression model controlling for the endogeneity of migration decisions. Our main finding is that the effect of expected occupational gain on the probability of rural-urban migration differs according to the rural sons' destination and parental occupational status: the sons from low status families were migrating motivated by expected occupational advancement. Sons from families with higher occupational status were motivated by expected occupational gains only in the case of rural-urban migration.